UHPLC-UV method validation for simultaneous quantification of vitexin and isovitexin from Santalum album L. leaves - Thi Kim Phung Phan; Minh Quan Le; Kien Duc Ngo (Tạp chí Khoa học Đại học Huế: Khoa học Tự nhiên)
Santalum album L. is a precious medicinal herb with high economic value and has been extensively cultivated in Vietnam in recent years. Studies have revealed that the leaves contain two main active ingredients vitexin and isovitexin, which have demonstrated significant potential in treating diabetes, cancer, and inflammation. To contribute to the standardization of the title medicinal herb and its formula, a simple, fast precise and selective method for the simultaneous quantification of vitexin and isovitexin using ultra-performance liquid chromatography (UHPLC) has been developed and validated. The quantification procedure was performed on a Hypersil GOLD aQ Column (3 μm; 150 × 2.1 mm) at 35°C, with a mobile phase of acetonitrile (A) and and water with 0.1% formic acid (B), a flow rate of 0.3 mL/min, a detection wavelength of 336 nm, and an injection volume of 3 µL. The gradient program was set to 0.0-15.0 minutes, transitioning from 5% to 35% A, and 15.0-20.0 minutes, transitioning from 35% to 5% A. Validation of the quantification procedure, following ICH Q2 (R2) guidelines, demonstrated that the method achieved specificity, accuracy, precision, and linearity, with a high correlation between the peak area and the concentrations of vitexin and isovitexin (R2 values of 0.9998, respectively). Thus, the developed method can be utilized to determine the content of vitexin and isovitexin in Santalum album L. leaves, contributing to the standardization of medicinal herbs.